Two new remarkable Callimicra Deyrolle, 1864 (Coleoptera: Buprestidae: Agrilinae) from Central America - Hespenheide, Henry A. (Zootaxa, 2013)
Collections from Panamá and the recent Arthropods of La Selva biodiversity inventory project in Costa Ricayielded specimens of two unusual species of the genus Callimicra Deyrolle, both of which exhibit striking color patterns. A brief review of the history of treatment of the genus is presented and the two new species are described and illustrated: Callimicra timmonsae sp.n. species, and C. prenai sp.n.